2019
DOI: 10.1080/10942912.2019.1653909
|View full text |Cite
|
Sign up to set email alerts
|

Quality attributes and related enzyme activities in peppers during storage: effect of hydrothermal and calcium chloride treatment

Abstract: The effects of hydrothermal (HT)-calcium chloride (CaCl 2) treatment on water loss, chlorophylls, L-ascorbic acid, total phenol, antioxidant capacity, malondialdehyde (MDA), peroxidase (POD), polyphenol oxidase (PPO), catalase (CAT), and phenylalanine ammonia lyase (PAL) of peppers were assessed for 32 days of storage at 8°C. The results showed two water populations corresponding to strongly immobilized water and weakly bound water were observed in all the peppers. Comparing with other treatments, HT-CaCl 2 tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…Catalase activity in green bell peppers is similarly enhanced by the application of calcium treatment during the storage period (Bagnazari et al, 2018). Similar to our result Xu et al (2019) showed higher CAT activity in the peppers treated with calcium chloride (CaCl 2 ) during storage.…”
Section: Resultssupporting
confidence: 92%
“…Catalase activity in green bell peppers is similarly enhanced by the application of calcium treatment during the storage period (Bagnazari et al, 2018). Similar to our result Xu et al (2019) showed higher CAT activity in the peppers treated with calcium chloride (CaCl 2 ) during storage.…”
Section: Resultssupporting
confidence: 92%
“…4% CaCl2 pre-harvest treatment resulted to higher total phenol, total flavonoid and antioxidant capacity on citrus (65). Hydrothermal-calcium chloride treatment resulted in higher L-ascorbic acid, total phenol content and powerful antioxidant ability on pepper (71). A combination of 50 °C of water dipping and 0.64% of calcium chloride is useful to retain bioactive components such as total phenolic, total flavonoid and quercetin of purple shallot (19).…”
Section: Effect Of Cacl2 Post Harvest Treatment On Total Phenolic Content Total Flavonoid Content Dpph Radical Scavenging Rate Of Banana mentioning
confidence: 99%
“…As compared to plants treated with different concentrations of calcium and sodium chloride, as well as plants not treated with calcium chloride, the plant's growth potential is increased with 100 mM NaCl at 3 mM CaCl 2 . However, plants treated with NaCl alone and without CaCl 2 , the plants react positively to combined stress by increasing proline and protein content while simultaneously decreasing leaf chlorophyll and carotenoids [8,23]. As shown by the growth of G. gracilis seedlings under alkali salts stress, salinity can inhibit root growth by altering the natural water potential, increasing ion toxicity, or causing an ion imbalance [49].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, chemical reactions between salt and the hydrated cementitious binder are possible. While NaCl appears to cause only a minor change in transport properties, CaCl 2 and MgCl 2 can cause much more drastic changes than NaCl [23,24,25]. Chemical phases (e.g., Friedel's salt, Kuzel's salt, calcium oxychloride, magnesium oxychloride, brucite, or magnesium silicate hydrate) may form in a solution containing CaCl 2 and MgCl 2 [22].…”
Section: Introductionmentioning
confidence: 99%